Kudus, local wisdom, and tobacco industry: historical trajectory of the employment relationship between scissoring workers and the company - Jefri Hari Akbar; Yusriyadi Yusriyadi; Soeganda Priyatna (Legality : Jurnal Ilmiah Hukum, 2025)
This research raises the paradox of labour relations in the traditional cigarette industry of Kudus, a city of kretek that inherits a work tradition based on local wisdom but is faced with rigid formal regulations. In practice, pressing operators work for millers—corporate workers who receive production-based wages—with a 60:40 share. Surprisingly, even though they do not have a formal working relationship with the company, scissoring workers still enjoy seemingly equal treatment, such as holiday allowances and work facilities. This phenomenon challenges the validity of Law No. 13 of 2003 concerning Employment, which ignores the uniqueness of local values in the labour relations framework. This study uses normative legal research methods with philosophical, conceptual, and statutory approaches to explore the tension between formal regulations and local practices coloured by kinship and social justice principles. The study results reveal that this employment relations model reflects a harmonious adaptation between tradition and the needs of the modern economy but is still vulnerable to narrow legal interpretations. This research provokes the idea that labour regulations in Indonesia work more like a tool of control rather than an instrument of empowerment. As such, a more inclusive and contextual legal framework is needed to accommodate the uniqueness of local practices without sacrificing labour protections. Kudus can serve as a social laboratory, showing that tradition and law can work in tandem to create substantive justice for the working community.